PENINGKATAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI MEDIA KERTAS KOKORU DI TK IT AL-IKHSAN PADANGMATINGGI, KOTA PADANGSIDIMPUAN. - Syifa Wardani; Hamidah; Dina Khairiah (STKIP Subang, 2026)
This study aims to improve the creativity of children aged 5–6 years through the use of kokoru paper media at TK IT Al-Ikhsan Padangmatinggi, Padangsidimpuan City. The research was motivated by the low level of children’s creativity, particularly in expressing ideas, imagination, producing varied works, and showing confidence in presenting their creations. This study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 15 children in group B. Data were collected through observation sheets, documentation, and assessment of children’s work, and analyzed descriptively using percentage calculations based on the Minimum Mastery Criteria (MMC ≥ 80). The results showed an increase in creativity achievement from 33.33% in the pre-cycle to 60% in cycle I, and significantly increased to 86.67% in cycle II. These findings indicate that kokoru paper media is effective in enhancing early childhood creativity and can be used as an engaging and meaningful learning medium.